UPAYA PEMERINTAH DESA UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA DI DESA UPA KECAMATAN TOBELO TENGAH KABUPATEN HALMAHERA UTARA - SURUAN, ARLIS LUTER; ROMPAS, WELSON; TULUSAN, FEMMY (Sam Ratulangi University, 2019)
The demand that the community suaya in the village increasingly play an active role in various village developmentplanning programs carried out by the village government starting from the planning process to decision making, untilthe development evaluation stage, is very clear and becomes a necessity to be implemented. Community participationin development can include forms such as; energy, thoughts, money, ideas, and opinions. From these forms ofparticipation, in the village of Upa, Central Tobelo Subdistrict, North Halmahera Regency, the form of communityparticipation was only in the implementation of village development, namely participation and time provided thatprogram participation was only represented by the BPD, and public figures. in providing participation in the form ofthoughts, ideas and opinions that are well made in making decisions for planning village development. The type ofresearch used in this study is qualitative research from the methods used so it can be assessed on the efforts of thevillage government to increase community participation in village development in Upa village, Tobelo TengahDistrict, North Halmahera Regency. Village development has been done well where the community was givendirection and motivation by the Head of the Village Upa to the community in the form of social motivation, as wellas motivation to give enthusiasm in participating in activities in the village such as in social services in the field. Inthe planning of a village development program the Village Head Upa in carrying out coordination and communicationtasks was carried out by holding village meetings held at the village office by inviting village representatives such asthe BPD chairperson, community leaders, and village officials. This meeting was held to discuss the developmentprograms that will be carried out in the village. The wage was given, the installation of phase I installation of streetlights, rehabilitation, concrete rabbis, sirtu roads, draenase and rehap houses were not suitable for habitation. Theprocess of community participation in village development Upa has been carried out with the stages of preparationand implementation of village development by involving community elements through their representatives.Keywords: Efforts of Village Government, Community Participation, Village Development